Young farmers and agroecology: A study on the Group Boa Vista’s Young Fair, Rio Grande do Sul, Brazil - Lara, Julio Cesar de; Eichler, Bruna Richter; Costa, João Paulo Reis; Gomes, Antonio Carlos; Schmitz, José Antonio Kroeff; Lara, Daniela Mueller de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
The increased demand for organic food grown in an ecological and sustainable way goes hand in hand with society's interest in safer and healthier products. In this sense, this study aimed to evaluate the profile of young organic food farmers participating in the Youth Fair in Boa Vista, in Santa Cruz do Sul/RS. The methodology addressed is of a qualitative exploratory nature using the technique of interviews and subsequent content analysis. This study was divided into four phases. In the first phase, meetings were held with the group of young farmers to expose the research, obtain data and information relevant to its development. In the second phase, semi-structured questionnaires were applied, as well as visits to rural properties were scheduled. From the answers obtained, the categorization of data was carried out, designated as the third phase. Finally, in the last phase, the analysis and interpretation of data was performed. The results show that the group, over the years of operation, exhibited aspects of strengthening and systematization regarding the commercialization of its products. The need for further development of factors related to the increase in productive capacity is perceived, with an increase in the cultivated area, an increase in technology, search for partnerships and possibilities for certification. At the same time, strengthening actions are needed, projecting the group of young farmers into the possibilities that exist in the municipality for the commercialization of cultivated products, enabling an increase in income for their families and promoting regional development.